A systematic review of observational studies of the association between pioglitazone use and bladder cancer. Issue 1 (15th November 2018) - Ripamonti, E.; Azoulay, L.; Abrahamowicz, M.; Platt, R.W.; Suissa, S.
Abstract: Aim: To conduct a systematic review of all observational studies on the effect of pioglitazone on the risk of bladder cancer. Methods: The MEDLINE and EMBASE databases were queried for papers published between 1 January 2000 and 30 October 2017. We took into consideration observational studies (both retrospective and prospective) that included participants with Type 2 diabetes prescribed anti‐hyperglycaemic drugs. Results: While some studies reported an association, others did not, and meta‐analyses of these studies showed a significantly increased risk; however, while meta‐analysis is a powerful and practical statistical tool, its results should be considered with caution when applied to widely heterogeneous studies. We describe how many of these studies are affected by different types of bias, most notably time‐related biases, which should preclude a pooled analysis that would result in biased estimation of the risk. Conclusions: Given existing data, it is not appropriate to pool the outcomes of highly heterogeneous studies and further rigorously conducted observational research is needed to clarify the role of pioglitazone use on the incidence of bladder cancer. What's new?: It is unclear from the literature whether or not pioglitazone is associated with bladder cancer. We addressed this issue, conducting a systematic review of observational studies. We found that some studies reported an association, others did not, but meta‐analyses of these studies detected a significant risk. We show how the clinical relevance of most research studies in this area is hampered by the presence of bias in their design, most notably time‐related bias. Further studies are needed to clarify the association, and pioglitazone should be prescribed with caution.